ICP-OES ANALYSIS OF ESSENTIAL, HEAVY, AND TRACE ELEMENTS IN THE MEDICINAL PLANTS OF UMERKOT DISTRICT, SINDH, PAKISTAN - Khadim Ali Gishkori; Saba Naz; Aftab Ahmed Kandhro; Aijaz Panhwar; Mohammad Younis Talpur; Muhammad Yousif Seelro; Nusrat Jalbani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
In this study, samples of medicinal plants from District Umerkot, Sindh, were analyzed for determining the concentrations of 17 essential elements, heavy metals, and trace metals such as Al, As, B, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Na, Ni, P, Pb, Se, and Zn. Determination of elemental profile of medicinal plants which are being used for therapeutic purposes in different regions. The analysis employed a 700 series Agilent inductively coupled plasma optical emission spectrometer (ICP-OES) coupled with ultrasonic CETAC U-6000AT + Nebulizer, following microwave-assisted acid digestion of the plant samples with MDS-6G closed microwave digester. The findings revealed significant concentrations of trace elements in medicinal plant extracts from the Umerkot, Sindh. Notably, Ipomoea Carnea samples exhibited elevated concentrations of essential elements, heavy metals, and trace metals such as 386.1, 0.0320, 0.8079,167.4, 0.194, 0.0016, 0.376, -1.932, 5.787, 33.72, 2.242, 15.56, 0.0115, 0.4936, 0.2371, 0.0494, 0.4785 mg/Kg, respectively. Fagonia indica samples displayed concentrations of 5.127, 0.0004, 0.6850, 121.7, 0.0036, 0.0024, 0.0181, 1.879, 1.844, 32.83, 0.3300, 11.83, 0.0019, 0.4054, 0.0054, 0.0202, and 0.0202 mg/Kg, respectively. However, Tinospora malabarica exhibited concentrations of 69.03, 0.0361, 1.555, 384.8, 0.0121, 0.0040, 0.0427, 0000, 7.100, 80.33, 3.242, 17.45, 0.0250, 0.14080, 9.550, 0.0181, 2.572 mg/Kg for Al, As, B, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Na, Ni, P, Pb, Se, and Zn, respectively. These elements can play a pivotal role in the plants' curative effects on human health.